2020
DOI: 10.3847/1538-4357/ab584d
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Rotation and Compactness of Progenitors on the Mass of Black Holes

Abstract: We investigate the impact of stellar rotation on the formation of black holes (BHs), by means of our population-synthesis code sevn. Rotation affects the mass function of BHs in several ways. In massive metal-poor stars, fast rotation reduces the minimum zero-age main sequence (ZAMS) mass for a star to undergo pair instability and pulsational pair instability. Moreover, stellar winds are enhanced by rotation, peeling-off the entire hydrogen envelope. As a consequence of these two effects, the maximum BH mass w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(132 citation statements)
references
References 107 publications
7
125
0
Order By: Relevance
“…The combined effect of PI and PPI is expected to carve a mass gap in the BH mass function, with lower boundary ∼40-65 M e and upper boundary 120 M e (Heger et al 2003;Belczynski et al 2016;Spera & Mapelli 2017;Woosley 2017Woosley , 2019Giacobbo et al 2018). The boundaries of the mass gap are highly uncertain because they depend on stellar evolution and on our understanding of CCSNe, PPI supernovae, and PI supernovae (Farmer et al 2019;Marchant et al 2019;Stevenson et al 2019;Mapelli et al 2020). Several formation channels might populate the mass gap.…”
Section: Pair-instability Mass Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined effect of PI and PPI is expected to carve a mass gap in the BH mass function, with lower boundary ∼40-65 M e and upper boundary 120 M e (Heger et al 2003;Belczynski et al 2016;Spera & Mapelli 2017;Woosley 2017Woosley , 2019Giacobbo et al 2018). The boundaries of the mass gap are highly uncertain because they depend on stellar evolution and on our understanding of CCSNe, PPI supernovae, and PI supernovae (Farmer et al 2019;Marchant et al 2019;Stevenson et al 2019;Mapelli et al 2020). Several formation channels might populate the mass gap.…”
Section: Pair-instability Mass Gapmentioning
confidence: 99%
“…Only the two metal-poor models with metallicity Z=10 −3 (dashed green line) and Z=10 −4 (purple solid line) undergo PI supernovae and leave no compact objects between m ZAMS ∼119-344 M e and ∼119-230 M e , respectively. The shaded area shows the PI mass gap, with the hatched regions corresponding to the uncertainty in current models (e.g., Farmer et al 2019;Mapelli et al 2020).…”
Section: Astrophysical Formation Channels and Implications For Stellamentioning
confidence: 99%
“…At the same time, a larger number of dynamical mergers reduces the number of light remnant BHs, M M 20 40 rem -  , making it harder to match observations and models in the M rem -a rem plane. (Belczynski et al 2016a;Woosley 2017Woosley , 2019Giacobbo et al 2018;Marchant et al 2019;Stevenson et al 2019;Renzo et al 2020), by stellar rotation (Mapelli et al 2020), by uncertainty on nuclear reaction rates (Farmer et al 2019), and by the collapse of a residual hydrogen envelope (Mapelli et al 2020). As a result, M BHmax might be as low as ∼40-45 M  (Belczynski et al 2016b) or as high as ∼65 M  (Giacobbo et al 2018).…”
Section: Impact Of the Formation Channelmentioning
confidence: 99%
“…Currently, significant work is conducted to study what can modify the predicted location of this mass gap, including uncertainties in nuclear reaction rates (Takahashi 2018;Farmer et al 2019), convection (Renzo et al 2020), the presence of a massive hydrogen envelope at iron-core collapse (Di Carlo et al 2019), and accretion after BH formation (van Son et al 2020). Regarding rotation, work has been done to study how it affects the evolution of a star prior to a PPISN or PISN (Chatzopoulos et al 2013;Mapelli et al 2020), but there is still a large uncertainty on how rotation affects the actual hydrodynamics of these events. Early work performed by Glatzel et al (1985) showed that rapid rotation can shift the boundaries of instability upward in mass, but provided no predictions on the resulting properties of BHs that formed through this process.…”
Section: Introductionmentioning
confidence: 99%